Penerapan Model Utaut dan Trust Terhadap Niat Pembayaran Zakat Secara Online - Frasya Nanda Tri Anisa; Dewita Puspawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study was to test and analyze the application of the UTAUT model (Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Condition) &  Trust and how it can affect the intention to pay zakat online. Data were collected primarily through an online questionnaire involving 184 respondents and then analyzed using Smart-PLS 4. The results of this study indicate that performance expectancy, effort expectancy, facilitating condition, and trust have an effect on behavioral intention, but social influence does not have an effect on behavioral intention